Exploring children's perceptions of barriers and facilitators to physical activity in rural Northwestern Ontario, Canada - Brenton Button; Suzanne Tillmann; Jason Gilliland (James Cook University, 2020)
Introduction: Low levels of physical activity among children are a significant public health concern in several industrialized nations. The current research body has failed to gather adequate information on various geographic regions. Understanding barriers and facilitators in different rural regions is imperative for creating successful physical activity interventions for children in rural areas. The purpose of this study is to explore rural children's perspectives on physical activity and to discuss barriers or facilitators to physical activity participation in rural Northwestern Ontario, Canada. Methods: Children (n=84) in Grades 4-8 (ages 8-14 years) in rural Northwestern Ontario participated in focus groups to discuss barriers and facilitators to physical activity. Twenty focus groups were conducted in schools. The focus groups were audio-recorded and transcribed verbatim. Transcripts were analyzed using thematic analysis. Subthemes were created based on the explicit content of the data and grouped to form broader themes. Results: Three key themes were identified: environment, social environment, and perceptions of safety. Environmental features include weather and the built environment. Social environment includes the role of friends and adults to either facilitate or restrict children's play. The fear of wildlife was pervasive across all focus groups and resulted in restricted independent mobility and physical activity. Conclusion: Rural children are typically under-represented in physical activity research. The findings of this study reveal that rural children experience some barriers to physical activity that are distinct from those of urban children. The findings suggest that researchers need to understand contextual nuances of the rural environment. Specific to the setting of Northwestern Ontario, these rural children could benefit from the addition of a skate park, indoor places to play, and more wildlife education.